Non-tuberculous mycobacteria (NTM) at Charlotte Maxeke Academic Hospital, 2010-2017 - Nqwata, Lamla (University of the Witwatersrand, Johannesburg, 2023)
Rationale: Diseases due to non-tuberculous mycobacteria (NTM) are difficult to diagnose and are not reportable in South Africa (SA), resulting in the disease burden and trends being under-appreciated. Objectives: To characterize NTM disease occurrence and trends in Johannesburg and to estimate end-of-treatment outcomes. Methods: A retrospective review of all clinical isolates that were positive for NTMs between 1 January 2010 and 30 June 2017 and the corresponding medical records of the patients at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) were analysed. A data collection form was designed, and data was collected based on information listed on the form. This was analysed using Graphpad Instat (Graphpad Inc, 3.1 version, San Diego, California, US) and STATA version 11, College Station, Texas, software. In descriptive analyses, two-tailed Fisher’s exact tests were used to compare categorical variables, while Kruskal-Wallis tests and Student’s T-test were used to compare continuous variables, as needed. Kaplan-Meier curves and log-rank tests were used to compare time-to-death, while Cox regression analyses were used in multivariate analyses of the same. Results: A total of 123 patients with positive NTM isolates were enrolled in this study. In this cohort, positive NTM isolates were found mostly in males (71; 57,7%), with a median age of 39 [Interquartile range 31.5-49.5] years. Mycobacteria avium complex (MAC) was the most common, isolated in 90 (75%) cases. Human immunodeficiency virus (HIV) infection, found in 96(80%) patients, and prior pulmonary tuberculosis (TB), found in 38(30%), were the common comorbidities. Overall, 27(22%) were successfully treated and 28(23%) died. In multivariate Cox regression analysis the adjusted hazard rates were 2.79 (95%CI 1.20 – 6.50) in those with low CD4 cell counts and 4.01 (95%CI 1.17 – 13.77) in those with unknown HIV test results. Receipt of antimicrobials did not significantly improve survival. Conclusion: Non-tuberculous mycobacteria (NTM) appear to be common in our setting and is associated with poor outcomes.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine (Internal Medicine), to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Non-tuberculous mycobacteria (NTM); Charlotte Maxeke Johannesburg Academic Hospital (CMJAH); Human Immunodeficiency Virus (HIV) infection; Mycobacteria Avium Complex (MAC); Prior pulmonary tuberculosis (TB); South Africa; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education